Theoretical Progress and Key Technologies of Onshore Ultra-Deep Oil/Gas Exploration. (June 2019) - Guo, Xusheng; Hu, Dongfeng; Li, Yuping; Duan, Jinbao; Zhang, Xuefeng; Fan, Xiaojun; Duan, Hua; Li, Wencheng
Abstract: Oil/gas exploration around the world has extended into deep and ultra-deep strata because it is increasingly difficult to find new large-scale oil/gas reservoirs in shallow–middle buried strata. In recent years, China has made remarkable achievements in oil/gas exploration in ultra-deep areas including carbonate and clastic reservoirs. Some (ultra) large-scale oil and gas fields have been discovered. The oil/gas accumulation mechanisms and key technologies of oil/gas reservoir exploration and development are summarized in this study in order to share China's experiences. Ultra-deep oil/gas originates from numerous sources of hydrocarbons and multiphase charging. Liquid hydrocarbons can form in ultra-deep layers due to low geothermal gradients or overpressures, and the natural gas composition in ultra-deep areas is complicated by the reactions between deep hydrocarbons, water, and rock or by the addition of mantle- or crust-sourced gases. These oils/gases are mainly stored in the original high-energy reef/shoal complexes or in sand body sediments. They usually have high original porosity. Secondary pores are often developed by dissolution, dolomitization, and fracturing in the late stage. The early pores have been preserved by retentive diageneses such as the early charging of hydrocarbons. Oil/gas accumulation in ultra-deep areas generally has the characteristics of near-source accumulation and sustained preservation. The effective exploration and development of ultra-deep oil/gas reservoirs depend on the support of key technologies. Use of the latest technologies such as seismic signal acquisition and processing, low porosity and permeability zone prediction, and gas–water identification has enabled the discovery of ultra-deep oil/gas resources. In addition, advanced technologies for drilling, completion, and oil/gas testing have ensured the effective development of these fields.